[OA196] First experimental validation of phase-attenuation hybrid X-ray imaging. (August 2018) - Contillo, Adriano; Arfelli, Fulvia; Brombal, Luca; Donato, Sandro; Longo, Renata; Rigon, Luigi; Taibi, Angelo
Abstract : Purpose: We propose a technique for the characterization of tissues, based on a hybrid phase contrast-attenuation imaging. The technique, first introduced in[1], makes use of a method for material basis decomposition proposed by Alvarez and Macovski[2] . We present a semi-analytical simulation of the imaging process, as well as a preliminary implementation on a set of radiographic images of a dedicated phantom. Methods: The phantom consists in a thin plastic plate composed of two "soft" materials, arranged in such a way to create a faint pattern of decreasing radiographic contrasts. The imaging was performed using synchrotron radiation (i.e. a quasi-parallel, monochromatic and coherent X-ray beam) and placing the phantom at different distances from the detector, so as to enhance the contribution of phase contrast. The images were acquired at the SYRMEP beamline of the Elettra synchrotron facility (Trieste, Italy). Results: The reconstructed composition of the phantom was compared to the results of the semi-analytical simulation, showing a good agreement with the theoretical expectations. In particular, the technique proved able to enhance the visibility of faint contrasts with respect to the standard attenuation-based imaging. Moreover, it provided a precise quantitative estimate of the local composition of the imaged phantom. Conclusions: The application of the basis decomposition method to the context of phase contrast imaging allows an effective rendering of a broad spectrum of radiographic patterns, from low frequency textures (which are captured by the attenuation effects) to high frequency details (highlighted by the phase shift effects). In addition, thanks to the simultaneous enforcement of two separate imaging channels, it also allows a two-component reconstruction of the imaged object.